Peran Struktur Anatomi Akar Dalam Adaptasi Tanaman Terhadap Cekaman Kekeringan - Marta Tristanti Mendrofa; Natalia Kristiani Lase (CV. SINAR HOWUHOWU, 2025)
This study aims to determine the effect of planting time (morning, noon, afternoon) on the early growth of corn (Zea mays L.). A descriptive qualitative method was used, involving field observation, interviews with farmers, and documentation. The findings revealed that planting in the morning led to faster and stronger early growth, marked by earlier germination, fresher leaves, and better root and shoot development. Morning conditions—cooler temperatures and higher humidity supported the seed’s imbibition and early metabolism. In contrast, noon planting showed the weakest performance due to heat and low humidity causing early stress. Afternoon planting yielded moderate results but was still less effective than morning planting. Interviews with farmers confirmed that the morning is considered the best planting time for corn. The study concludes that choosing the right planting time, especially in the morning, is a key factor in supporting early plant development and ensuring successful cultivation in the field.